2021
DOI: 10.7150/jca.62394
|View full text |Cite
|
Sign up to set email alerts
|

Decreased interferon regulatory factor 6 expression due to DNA hypermethylation predicts an unfavorable prognosis in clear cell renal cell carcinoma

Abstract: Background: Emerging evidences have indicated that IRF6, as a member of the Interferon regulatory factors (IRFs) family, plays important roles in a variety of tumors. However, the expression status of IRF6 and its prognostic value in clear cell renal cell carcinoma (ccRCC) remain unclear. Methods: In this study, we used TCGA-KIRC, GEO and TIP databases and immunohistochemistry staining to determine the expression profile, clinico-pathological features and prognostic value of IRF6 in ccRCC. MSP and demethylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…It has been reported that overexpression of PDHA1 can inhibit aerobic glycolysis and result in mitochondria-mediated apoptosis in hepatocellular cancer 41 . Additionally, other surveys elucidated that PDHA1 might play an antitumour role in cancer and that low expression of PDHA1 predicted a poor outcome in these tumours 42 , 43 . However, compared to Warburg effect-dependent cancer cells, several kinds of cancer rely on the TCA cycle as well.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that overexpression of PDHA1 can inhibit aerobic glycolysis and result in mitochondria-mediated apoptosis in hepatocellular cancer 41 . Additionally, other surveys elucidated that PDHA1 might play an antitumour role in cancer and that low expression of PDHA1 predicted a poor outcome in these tumours 42 , 43 . However, compared to Warburg effect-dependent cancer cells, several kinds of cancer rely on the TCA cycle as well.…”
Section: Discussionmentioning
confidence: 99%
“…FDX1 impacted the prognosis of lung adenocarcinoma and was closely related to glucose metabolism, fatty acid oxidation and amino acid metabolism [ 71 ]. Decreased PDHA1 expression was associated with poor overall survival of individuals with oesophageal squamous cell carcinoma, prostate cancer, ovarian carcinoma, and GC [ [72] , [73] , [74] , [75] ]. Likewise, in this study, the risk score of four cuprotosis genes, LIAS, FDX1, PDHA1 and DLD, could predict GC prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that the expression level of the PDHA1 gene is elevated in various cancers such as ovarian cancer, and high expression levels are closely related to the malignancy and prognosis of tumors. In addition, the PDHA1 gene is involved in regulating the oxidative stress response of tumor cells, enabling them to acquire stronger antioxidant capabilities and survival advantages, thereby promoting tumor cell growth and metastasis ( 82 , 83 ). Some studies have also suggested that the PDHA1 gene may act as a potential tumor suppressor gene in gastric and renal cell carcinoma, and its mutations or deletions can lead to disruptions in cellular energy metabolism and inhibition of autophagy and apoptosis, and promote tumor formation and development ( 84 , 85 ).…”
Section: Discussionmentioning
confidence: 99%